Interferencia del Herpesvirus equino 1 (EHV-1) en la apoptosis inducida - Scrochi, M.R. (2013)
Apoptosis is a programmed cell death that can be triggered by many factors, both internal and external. Viral infections are included among the latter. Some alphaherpesvirus have developed several strategies to retard or inhibit cell death and thus the virus benefits itself by staying longer in the cell. So far, no mechanisms have been identified related to modulation of cell death during infection with equine herpesvirus type 1 (EHV-1). The aim of the present study was to describe the effect produced by the infection with EHV-1 on apoptosis-induced cell cultures. Assessment of apoptosis was performed by DNA laddering, the Annexin V/propidium iodide (PI) determination and the cytokeratin 18 cleavage analysis using immunofluorescence techniques. Results indicate a possible interference of EHV-1 with apoptotic cell death in the middle of its replication cycle, being increased by its end.